Reading perspectives moderate text-belief consistency effects in eye movements and comprehension. Issue 2 (7th February 2023) - Abendroth, Johanna; Richter, Tobias
ABSTRACT: Readers often prioritize processing and comprehension of information perceived as relevant to a particular intention. Using a repeated-measurement study, we investigated how readers' prior beliefs and external reading perspectives influence processing and comprehension of belief-relevant texts on two socioscientific controversies. University students read belief-relevant texts from a belief-consistent perspective in one experimental session and from a belief-inconsistent reading perspective in another. Eye tracking was used to measure immediate and delayed processing and a sentence verification task was used to measure comprehension. Results revealed longer first-pass reading times for belief-inconsistent claims compared to belief-consistent claims, especially in the belief-inconsistent reading perspective. Longer lookbacks on belief-consistent claims were found in the belief-consistent reading perspective but similar lookback times for both types of claims in the belief-inconsistent reading perspective. We further found better comprehension for belief-consistent information in the belief-consistent reading perspective but balanced comprehension levels in the belief-inconsistent reading perspective.